2006
DOI: 10.1111/j.1745-4549.2006.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinization and Viscosity Behavior of Single-Screw Extruded African Breadfruit (Treculia Africana) Mixtures

Abstract: Mixtures of African breadfruit (Treculia africana), corn and soybean were extruded in a single‐screw extruder. Feed composition (fc), feed moisture (fm) and screw speed (ss) were three process variables investigated at five level conditions. The fc was at 40:5:55, 55:5:40, 70:5:25, 85:5:10 and 100:0:0% (breadfruit, corn and soybean, respectively), fm was at 15, 18, 21, 24 and 27% while ss was at 100, 120, 140, 160 and 180 rpm level conditions using a second‐order response surface composite design. Process vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…The estimation is that by 2050 the world population will be nine (9) billion. That is three (3) billion higher than the current figure of six (6) billion. It has also been estimated that there will be an exponential growth more in the cities in developing countries, especially, in Africa and Asia [1] where food insecurity as well as child mortality due to malnutrition is endemic [2].…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…The estimation is that by 2050 the world population will be nine (9) billion. That is three (3) billion higher than the current figure of six (6) billion. It has also been estimated that there will be an exponential growth more in the cities in developing countries, especially, in Africa and Asia [1] where food insecurity as well as child mortality due to malnutrition is endemic [2].…”
Section: Introductionmentioning
confidence: 67%
“…This forest tree legume is a member of the Mullberry family, Moraceae [6] and is known in Ibibio as 'Ubong Mbakara' and in Igbo as 'Ukwa'. The seed is widely consumed in the South-eastern Nigeria as snacks or pulverized and added to soups as thickener.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, extrusion cooking relies on conversion of shear and frictional energy to heat energy, which cooks (Grenus et al 1993) and improves digestibility by denaturing the protein, exposing new sites for enzyme attack and by inactivating inhibitors (Lorenz et al 1980;Rackis et al 1986;Iwe and Ngoddy 2000). The proximate composition, amino acid profile, and anti-nutritional composition of raw and extruded African breadfruit-corn-soybean mixtures had been reported in literature (Nwabueze 2006;Nwabueze 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Its combination with soybean alone or soybean and corn to produce acceptable and improved protein quality products through fermentation and germination (Ariahu et al 1999) and extrusion cooking (Nwabueze 2006) had been reported. In addition, the potential for producing non-alcoholic beverage (Ejiofor et al 1988) and as raw material for bread making, cake, and cookies (Lawal and Bassir 1986;Giami et al 2004) had earlier been reported.…”
Section: Introductionmentioning
confidence: 97%